Physiological characteristics and transcriptomic analyses of alfalfa root crown in wintering - Wang, Xiaolong; Chai, Hua; Li, Shasha; Xu, Yanxia; Wu, Yue; Wang, Jianli; Yang, Zhao (Frontiers in Plant Science, 2024)
Background: Alfalfa, scientifically identified as Medicago sativa, is repeatedly referred to as the "king of forages". Because of its tight relationship to winter hardiness, the alfalfa's root crown plays a significant role as a storage organ over the winter. At present, it is still unknown what molecular process makes the alfalfa root crown resistant to cold. This study was aimed to study these knowledge gaps. Using RNA sequencing (RNA-Seq) technology, significant genes associated with cold hardiness were found.Methods: According to the random block design, Longmu 806 alfalfa and Sardi alfalfa were planted in regional experiments. Under the condition of low-temperature treatment in winter, the differentially expressed genes (DEGs), winter survival rate (WSR), and physiological characteristics were, in turn, calculated by RNA-Seq, chemical analysis, and field investigation.The WSR of the Longmu 806 alfalfa was 3.68-fold greater than that of the Sardi alfalfa. The jasmonic acid (JA), soluble sugar (SS), proline (Pro), and glutathione (GSH) concentration in the roots of Longmu 806 alfalfa was more than the same amount in Sardi alfalfa in other words P is less than 0.05. An entire set of 878 DEGs related to winter hardiness was found by statistical analysis. Among them, 463 DEGs showed an increase in expression, whereas 415 DEGs showed a decrease in expression. The metabolic pathways' examination presented that the DEGs (MsERF1, MsCHIB, MsJAZ, MsAOC, MsGST, MsINV, MsTPS, and MsOAT) were linked to the pathways of "plant hormone signaling transduction", "Amino sugar and nucleotide sugar metabolism", and "glutathione metabolism". Furthermore, the physiological changes in JA, SS, Pro content, and GSH were influenced by the dynamic transcription profile of LT (low-temperature) resistance-related genes.